The role of Bacillus species in the management of plant-parasitic nematodes - Prabhakaran Vasantha-Srinivasan; Ki Beom Park; Kil Yong Kim; Woo-Jin Jung; Yeon Soo Han (Frontiers in Microbiology)
Plant-parasitic nematodes (PPNs), including root-knot nematodes (Meloidogyne spp.), cyst nematodes (Heterodera and Globodera spp.), and other economically significant nematode species, pose severe threats to global agriculture. These nematodes employ diverse survival strategies, such as dormancy in cysts or robust infective juvenile stages. Consequently, their management is challenging. Traditional control methods, such as the use of chemical nematicides, are increasingly scrutinized because of environmental and health concerns. This review focuses on the specific mechanisms employed by Bacillus spp., including nematicidal compound production, systemic resistance induction, and cuticle degradation, to target root-knot and cyst nematodes. These mechanisms offer sustainable solutions for managing nematodes and promoting soil health by enhancing microbial diversity and nutrient cycling. An integrated approach leveraging Bacillus-based biocontrol is proposed to maximize efficacy and agricultural sustainability.